2015
DOI: 10.1364/oe.23.014520
|View full text |Cite
|
Sign up to set email alerts
|

Anderson localization of electromagnetic waves in randomly-stratified magnetodielectric media with uniform impedance

Abstract: The propagation and the Anderson localization of electromagnetic waves in a randomly-stratified slab, where both the dielectric permittivity and the magnetic permeability depend on one spatial coordinate in a random manner, is theoretically studied. The case where the wave impedance is uniform, while the refractive index is random, is considered in detail. The localization length and the disorder-averaged transmittance of s and p waves incident obliquely on the slab are calculated as a function of the incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…The value of the slope suggests an exponent v′ 2, i.e., ξ ∝ sin −2 θ 0 . This result is distinctly different from those found in Hermitian impedance-matched 1D random systems [31] and pseudospin-1 system [32], in which the exponents found are both v′ 4 rather than v′ 2.…”
Section: Anomalous Anderson Localization Behaviorscontrasting
confidence: 98%
See 1 more Smart Citation
“…The value of the slope suggests an exponent v′ 2, i.e., ξ ∝ sin −2 θ 0 . This result is distinctly different from those found in Hermitian impedance-matched 1D random systems [31] and pseudospin-1 system [32], in which the exponents found are both v′ 4 rather than v′ 2.…”
Section: Anomalous Anderson Localization Behaviorscontrasting
confidence: 98%
“…In both scenarios, it is expected that the presence of coherent backscattering can lead to the Anderson localization of waves, i.e., the transmission will decay exponentially to zero when the sample is sufficiently large. Our results will be compared with the Anderson localization behaviors found in some special Hermitian random systems, where localization length is also known to be infinite at normal incidence such as random layered media with the same impedance in all layers [31] and pseudospin-1 systems in 1D random potential [32,33].…”
Section: Introductionmentioning
confidence: 96%
“…Similar methods have been applied in previous studies of the localization of electromagnetic waves in random dielectric media. 41,[47][48][49] We assume that an electron plane wave is incident from a uniform region (x > L) onto the random region (0 ≤ x ≤ L) obliquely at an angle θ and transmitted to another uniform region (x < 0). The wave function ψ A (or equivalently ψ B ) in the incident and transmitted regions can be expressed in terms of the reflection coefficient r and the transmission coefficient t:…”
Section: Invariant Imbedding Methodsmentioning
confidence: 99%
“…However, it has been found that this conclusion is not always true in more general random systems and there exist various situations where some states are not exponentially localized, but are either extended or critically localized. Representative examples include the cases where distinct kinds of impedance matching phenomena such as the Brewster anomaly [15][16][17][18][19][20] and the Klein effect [21][22][23][24] happen or the random potential is spatially correlated with short-or long-range correlations [25][26][27][28][29][30][31][32][33]. For instance, it has been demonstrated both theoretically and experimentally that there exist extended states at two energy values in the 1D random dimer model which contains a special type of shortrange correlated disorder [25,26].…”
Section: Introductionmentioning
confidence: 99%